Effective Reading Interventions for Slow Learners : Sight Word and Phonemic Awareness Approaches - Purnomo, Jihan Salsabila; Royanto, Lucia R.M. (Jurnal Paedagogy, 2025)
This study investigates the effectiveness of sight words and phonemic awareness learning, delivered through drilling method, in enhancing reading skills in a child identified as slow learner. The subject of this study is a 9-year and 10-month-old boy in the fourth grade of elementary school. The research method employed in this study is a single-case intervention design. The process involved various assessment stages, including detailed observations, structured interviews with teachers and parents, and comprehensive psychological tests to understand the unique challenges faced by the subject. To evaluate the effectiveness of these interventions, both pre-tests and post-tests were administered, which assessed the subject's reading skills in terms of accuracy and reading speed. The analysis of the results revealed significant progress in the subject's reading abilities following the interventions. Notably, improvements were observed in both the accuracy of reading sight words and the overall speed at which the subject could read. These positive findings underscore the effectiveness of focused teaching strategies, demonstrating that systematic and structured interventions can substantially enhance reading abilities in slow learners. The study highlights the importance of tailoring educational approaches to meet the specific needs of slow learners, in order to maximize their potential and improving their overall academic performance. Furthermore, these results suggest that educators can employ similar methods to support other students facing similar challenges in reading.